German Economy: Upswing has gained breadth but will not hold pace - Ferdinand Fichtner; Karl Brenke; Marius Clemens; Simon Junker; Claus Michelsen; Thore Schlaak; Kristina van Deuverden (DIW Economic Bulletin, 2017)
The upswing of the German economy continues and since the beginning of 2017, even at a somewhat faster pace. Sharp gains in employment are still driving consumption. And companies are investing significantly more in machines and facilities. Many global risks that previously limited the propensity to invest-in Germany and many other countries-have vanished. And the euro area is also finally feeling the upswing. The German export industry in particular is enjoying the benefits. The German Institute for Economic Research (DIW Berlin) is thus raising its forecast for German GDP and now anticipates a plus of 2.2 percent for this year. Although the momentum will gradually slow down toward the end of the forecast horizon, Germany's annual growth for 2018 should be of the same magnitude. All in all, the economy is booming but not to the point of overheating-wage and price movement is restrained.
Keywords: E32; E66; F01; 330; business cycle forecast; economic outlook